Analisis Website Quality Terhadap Online Booking Intention Melalui E-Trust Pada Website Online Travel Agent - Elah Elah; Asep Muhamad Ramdan; Nor Norisanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Tourism travel at this time has become a lifestyle for the community, along with the times, the tourism sector continues to grow along with the development of information, transportation and technology. Which makes it easier for people to do the buying and selling process digitally such as the help of e-commerce and websites. The tourism industry is currently very tight, making the competitiveness between destination managers even higher. So that Tiket.com as one of the destination providers is not always the first choice of the community in using these travel services which has an impact on decreasing consumer transactional interest in Tiket.com. The purpose of the study is to ascertain how website quality and e-trust as mediation affect online booking intention. This research uses quantitative research methods with a descriptive approach. The sampling method used was the probability sample approach used, by distributing questionnaires to 180 tiket.com application users in Sukabumi City. The data analysis technique used was using SmartPLS software version 3.2.9. The results of this research show that the significant influence between website quality can increase online booking intention on Tiket.com application users in Sukabumi City.